Hepatosplenic Abscess From in Poorly Controlled Diabetic - Chidinma Ejikeme MD; Onyeka Nwachukwu MD; Sarah Ayad MD; Payal Rath MD; Ifunanya Ejikeme Medical Student; Julius Salamera MD (SAGE Publishing, 2021)
Invasive Klebsiella pneumoniae infection and pyogenic liver abscess in patients with underlying diabetes mellitus has been well described over the past 3 decades, predominantly in the Southeast Asian population, especially in Taiwan and Korea. K pneumoniae has now become the most common causative pathogen of pyogenic liver abscess in Asian countries. This shift from Escherichia coli to K pneumoniae may also be increasingly occurring in the United States of America and European countries. Compared with the >80% incidence described in Taiwan, the incidence in the United States is still reported to be lower, around 30% to 40%. However, as more evidence and reports come to light, it has become of prime importance to recognize Klebsiella as a significant emerging cause of metastatic infections in patients with uncontrolled diabetes in the United States and not just Southeast Asia, given the significant morbidity and mortality associated with the condition. In this article, we discuss the case of a 53-year-old African American female who presented with diabetic ketoacidosis and was subsequently found to have K pneumoniae pyogenic liver abscess primarily in the left hepatic lobe, bacteremia, and septic metastases to the spleen. She required extensive percutaneous drainage of abscesses and a prolonged course of multiple antibiotics. This case illustrates the growing incidence of invasive K pneumoniae infection in the diabetic population in the United States, and better patient outcomes from prompt recognition and treatment.